2005
DOI: 10.1111/j.0022-202x.2005.23784.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Light (UVB and UVA) Induces the Damage-Responsive Transcription Factor CHOP/gadd153 in Murine and Human Epidermis: Evidence for a Mechanism Specific to Intact Skin

Abstract: C/EBP-homologous protein (CHOP)/gadd153 (or CHOP) is a transcription factor induced by endoplasmic reticulum (ER) stress. Forcible overexpression of CHOP causes apoptosis in keratinocytes in culture. Here, we asked whether CHOP might be increased in the skin after UVB (280-320 nm) exposure, thus implicating CHOP in sunburn cell (SBC) formation. SKH-1 hairless mice were exposed to a ultraviolet (UV) source (80 mJ per cm2; approximately 74% UVB, approximately 16% UVA), and skin biopsies examined by immunohistolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…Previously, Kaufman and colleagues reported that UVC (254 nm) activates the PERK pathway in COS-1, MCF-7 and HIT cells (Wu et al, 2002), and Maytin and colleagues showed that UV light consisting of 74% UVB (280-320 nm) and 16% UVA induced the transcription of CHOP in murine epidermis (Anand et al, 2005). Recently, Kanekura and colleagues revealed that UVB (around 302 nm) activated the ATF6 and IRE1 pathways, but not the PERK pathway in human keratinocytes (Mera et al, 2010); however, to the authors' knowledge, this is the first report demonstrating that UVA (315-400 nm) activates the ER stress response in eukaryotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Kaufman and colleagues reported that UVC (254 nm) activates the PERK pathway in COS-1, MCF-7 and HIT cells (Wu et al, 2002), and Maytin and colleagues showed that UV light consisting of 74% UVB (280-320 nm) and 16% UVA induced the transcription of CHOP in murine epidermis (Anand et al, 2005). Recently, Kanekura and colleagues revealed that UVB (around 302 nm) activated the ATF6 and IRE1 pathways, but not the PERK pathway in human keratinocytes (Mera et al, 2010); however, to the authors' knowledge, this is the first report demonstrating that UVA (315-400 nm) activates the ER stress response in eukaryotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…UVA, UVB, and UVC are all capable of stimulating ROS production 73 as well as overlapping stress response pathways 74 including ER stress. 75 Which particular subtle difference distinguishes between ICD and non-ICD is an avenue worth investigating.…”
Section: Ultraviolet C Lightmentioning
confidence: 99%
“…UV irradiation (17,19), oxidative stress, and wound injury (20), also initiate ER stress responses including downstream activation of the transcription factor, NF-B (16). Because several stressors also up-regulate CAMP expression and because ER stress/activation ubiquitously occurs in mammalian cells, we hypothesized here that ER stress-mediated signals could stimulate CAMP expression in epithelial cells exposed to external perturbations, thereby restoring or enhancing antimicrobial defense barrier(s).…”
mentioning
confidence: 99%